EXTRINSIC MOTIVATION, KNOWLEDGE SHARING, AND INNOVATIVE BEHAVIOR: A MODEL FOR ENHANCING EMPLOYEE PERFORMANCE - Andari, Andari; Nafiudin, Nafiudin; Pratami, Eggi (Jurnal Riset Bisnis dan Manajemen, 2026)
This study aims to examine the influence of extrinsic motivation and knowledge sharing on employee performance, with innovative behavior as a mediating variable. The approach used is quantitative, with an explanatory research design. Data were collected from 65 employees of a construction company via questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study shows that extrinsic motivation and knowledge sharing positively contribute to innovative behavior and that innovative behavior significantly influences employee performance. Recognizing these findings can inspire researchers and practitioners to foster motivation and knowledge sharing for better performance. However, knowledge sharing does not directly affect performance, and innovative behavior does not mediate the relationship between extrinsic motivation and performance. Conversely, innovative behavior has been shown to act as a significant mediating variable in influencing knowledge sharing and employee performance.